The Economic Effects of the Montgomery Bus Boycott - Kush K. Jenkins; Carlos J. Whitfield; Anthony Johnson (Center for Open Science, 2025)
This paper reexamines the economic effects of the Montgomery Bus Boycott, an event often celebrated for its moral and social significance, yet underexplored in terms of its fiscal implications. We assess the hypothesis that the Boycott had no measurable impact on the City of Montgomery's public finances and find compelling evidence to the contrary. Our analysis demonstrates that the Boycott significantly contracted municipal revenue and simultaneously escalated public expenditures, particularly in policing and fire services, driven by the city's "get tough" policy response. Using historical financial records and time-series forecasting (ARIMA), we quantify the growing fiscal strain experienced by the city. Although Montgomery maintained budget surpluses during the Boycott period, projections indicate a rising probability of deficits had the protest continued beyond its resolution. These findings highlight the economic leverage wielded by organized civil resistance and underscore the material costs incurred by municipal governments when confronting movements for racial justice.
Keywords: N42; H72; D74; B52; I38; H75; Z18; R51; 330; Economic History; Montgomery Bus Boycott; Civil Rights Movement; Fiscal Impact; Martin Luther King; Rosa Parks; Protest Economics; Time-Series Forecasting; African American History; Local Government Budgets